2009
DOI: 10.1051/0004-6361/200912753
|View full text |Cite
|
Sign up to set email alerts
|

Detection of three periodicities in a single oscillating coronal loop

Abstract: Context. TRACE 171 Å observations of transverse loop oscillations on May 13, 2001 have been studied by De Moortel & Brady (2007). They found hints of 3 periodicities present in this event.Aims. The aim of this article is to improve the analysis, and measure the periodicities more accurately in order to do coronal seismology. Methods. We create multiple (x, t)-slices across the loop, and determine the oscillatory parameters within those slices. We then use statistical methods to reduce the errors on the measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The BCS oscillations have periods and damping times consistent with those for transverse loop oscillations (TLOs). Transverse oscillation periods longer than 10 min have been observed (Hori et al 2005;De Moortel & Brady 2007;Van Doorsselaere et al 2009;Verwichte et al 2009Verwichte et al , 2010, which puts them in the range of those periods observed with SUMER. Tothova et al (2011) detected in combined TRACE and SUMER observations the copresence of slow and transverse standing modes, which manifested themselves as oscillations in Doppler velocity in an emission line sensitive to hot plasma of 6 MK.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…The BCS oscillations have periods and damping times consistent with those for transverse loop oscillations (TLOs). Transverse oscillation periods longer than 10 min have been observed (Hori et al 2005;De Moortel & Brady 2007;Van Doorsselaere et al 2009;Verwichte et al 2009Verwichte et al , 2010, which puts them in the range of those periods observed with SUMER. Tothova et al (2011) detected in combined TRACE and SUMER observations the copresence of slow and transverse standing modes, which manifested themselves as oscillations in Doppler velocity in an emission line sensitive to hot plasma of 6 MK.…”
Section: Introductionmentioning
confidence: 70%
“…In particular, the density stratification inside coronal loops is related to the ratio of the fundamental period (P 1 ) to the period of the second harmonic (P 2 ). Another observation of higher order harmonics in TLOs was made by De Moortel & Brady (2007) for which a repeat analysis was conducted by Van Doorsselaere et al (2009). This spatially resolved TRACE observation allowed three periodicities to be detected (which were identified as the fundamental mode and both the first and second harmonics).…”
Section: Introductionmentioning
confidence: 99%
“…1, one may deduce that except for one all observations have τ/P ≥ 1. (There is one observation with a smaller quality factor, but the damping rate has a high uncertainty, Van Doorsselaere et al 2009.) However, an estimate of (τ/P) min based upon the observed lower limit in τ/P relies on only a few measurements.…”
Section: The Quality-factor Probability Density Distributionmentioning
confidence: 99%
“…Fortunately, there have been some signatures of overtones in coronal loop standing kink waves detected in TRACE data (see e.g. Verwichte et al 2004;De Moortel & Brady 2007;Van Doorsselaere et al 2009). For a particularly clear example of the first overtone damping before the fundamental mode, that could be explained by resonant absorption attenuating the higher harmonic faster, see the Morlet wavelet transform in Fig.…”
Section: Inhomogeneous Magnetic Cylindermentioning
confidence: 99%